Effect of Brand Awareness and Brand Loyalty on the Purchase Decision of Adidas Brand Sport Shoes by Bandung City Adidas Lovers - Deden Muhammad Adam; Adam Aditya Mandala; Muhamad Bayu Hasan Basri (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
The universe influences the global economic cycle, and consumer decisions are increasingly complex when choosing or buying competing brands in international markets. This study was conducted to analyze the effect of brand awareness and loyalty on purchasing Adidas brand sports shoes, then determine which variables have a core influence on consumer decisions to buy Adidas branded sports shoes. Methods of collecting data with a questionnaire. The population in this study were fans of the